META-ANALYSIS OF THE EFFECT OF PROBLEM-BASED LEARNING (PBL) ON CHEMISTRY LEARNING OUTCOMES - Siska Alvionita (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to re-analyze the effectiveness of the Problem Based Learning (PBL) learning model on students' Chemistry learning outcomes. The type of research is meta-analysis research. The subjects of this study are 14 articles that have been published over the past 10 years by several national and international journals and can be accessed online through ERIC and Google Scholar. The research instrument used is a coding sheet. The method of information analysis uses quantitative descriptive analysis with effect size guidelines. After getting the effect size value, then the effect size can be categorized into levels or categories of effect size. The results of this meta-analysis study show that the PBL learning model is very influential in improving students' Chemistry learning outcomes with the lowest percentage of 5.44% to the highest reaching 120.59%. Based on the results of the meta-analysis, it also shows that if the PBL learning model has a high influence, there are students' Chemistry learning outcomes when viewed through the effect size by getting an average of 2.659984005. At the high school education level, the average effect size is 2.571626429 and the university level is 3.190129466. The average effect size of research published in Indonesia has an average effect size of 2.642521674 and research published abroad has an average effect size of 2.683267114. It can be concluded that the PBL learning model is very effective in learning Chemistry to improve student learning outcomes.